2011
DOI: 10.1159/000324701
|View full text |Cite
|
Sign up to set email alerts
|

Central Serous Chorioretinopathy with Subretinal Deposition of Fibrin-Like Material and Its Prompt Response to Ranibizumab Injections

Abstract: Purpose: Central serous chorioretinopathy (CSCR) manifests as neurosensory detachment of the macula and can be attributed to focal or multifocal leakage in the retinal pigment epithelium (RPE). Fibrin accumulation in the subretinal space is an unusual and heretofore unreported visually damaging manifestation of severe CSCR. Methods: The patient was followed up with the use of biomicroscopy, fluorescein angiography, and optical coherence tomography (OCT). Results: A 32-year-old woman was referred to our departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Contrary to previous reports, however, the result was disappointing as the patient's BCVA continued to decline [10, 14]. Another possible therapeutic option in our patient was the use of focal argon laser coagulation at sites of leakage [1].…”
Section: Discussioncontrasting
confidence: 70%
“…Contrary to previous reports, however, the result was disappointing as the patient's BCVA continued to decline [10, 14]. Another possible therapeutic option in our patient was the use of focal argon laser coagulation at sites of leakage [1].…”
Section: Discussioncontrasting
confidence: 70%
“…Another possible mechanism involved is a choriocapillary endothelial hyperpermeability which could justify the prompt response to the anti‐VEGF treatment. Of note, Symeonidis et al reported an interesting case of central serous chorioretinopathy with fibrin‐like material and absence of choroidal neovascularisation which promptly responded to one ranibizumab injection. However, we cannot exclude with certainty that the hyper‐reflective material was secondary to the presence of a small area of choroidal neovascularisation which was not detectable on the currently available imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Peripapillary subretinal space is a part of the subretinal space. Subretinal space is an important structure to the extent that so many reports referred to it such as central serous chorioretinopathy [6].…”
Section: Joj Ophthalmologymentioning
confidence: 99%